The Industrial Relations Implications of Privatization: The Case of Canada Post - White, Jerry; Janzen, Russell (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 2000)
In February 1997, Canada Post privatized its ad-mail services and in the process terminated 10,000 Canadian Union of Postal Workers. These events became a part of the central driving force which derailed contract negotiations and led to the November 1997 postal strike. The purpose of this article is to expose the process and consequences of this major event in the industrial relations of Canada Post; to examine the role and positions of the three major institutions involved — the government, the corporation (Canada Post) and the Canadian Union of Postal Workers (CUPW), and to explore the implications of privatization with regards to industrial relations in Canada Post. The article also documents the fate of the 10,000 workers through a survey of their status six months after the privatization.